2006
DOI: 10.1111/j.1462-2920.2006.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic diversity associated with carbonates and fluid–seawater interface in Lost City hydrothermal field

Abstract: Lost City is a unique off-axis hydrothermal vent field characterized by highly alkaline and relatively low-temperature fluids that harbours huge carbonate chimneys. We have carried out a molecular survey based on 18S rDNA sequences of the eukaryotic communities associated with fluid-seawater interfaces and with carbonates from venting areas and the chimney wall. Our study reveals a variety of lineages belonging to eight major taxa: Metazoa, Fungi, Heterokonta (Stramenopiles), Alveolata, Radiolaria, Cercozoa, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
157
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(166 citation statements)
references
References 27 publications
7
157
1
1
Order By: Relevance
“…Atkins (2000) suggested that flagellate protozoans could maintain metabolism within the extreme conditions of hydrothermal vents with high concentrations of, e.g., sulphide in the water column. This conclusion is strengthened by the high protistan diversity described in López-García et al (2007). Bennet et al (2013) also found an increase in total organic carbon (TOC) compared to surrounding waters.…”
Section: Ecological Assessmentmentioning
confidence: 57%
See 1 more Smart Citation
“…Atkins (2000) suggested that flagellate protozoans could maintain metabolism within the extreme conditions of hydrothermal vents with high concentrations of, e.g., sulphide in the water column. This conclusion is strengthened by the high protistan diversity described in López-García et al (2007). Bennet et al (2013) also found an increase in total organic carbon (TOC) compared to surrounding waters.…”
Section: Ecological Assessmentmentioning
confidence: 57%
“…Although eukaryotic micro-organisms in Nordic Seas plumes have not been studied before, several other studies have focused on the effect of hydrothermal plumes from other parts of the world on both the mesozooplankton (Berg and Van Dover 1987;Burd and Thomson 1995;Burd et al 2002;Vinogradov and Vereshchaka 2005;Olsen et al 2013) and the microplankton (Atkins 2000;López-García et al 2007;Bennet et al 2013). While hydrothermal vents clearly contribute to increasing the available metabolic energy, how this increased energy affects the biodiversity remains unclear.…”
Section: Ecological Assessmentmentioning
confidence: 99%
“…Since that time, additional nonculture-based studies describing eukaryotic diversity in a variety of ecological settings have emerged. Among these habitats are: a multipond saltern (Casamayor et al, 2002), rice soil (Murase et al, 2006), an anoxic Norwegian fjord (Behnke et al, 2006), Mediterranean sea water (Diez et al, 2001), a sulfide-rich freshwater spring (Luo et al, 2005), a seafloor hydrothermal vent field (Ló pez- García et al, 2007) and an anaerobic aquifer polluted with landfill leachate (Brad et al, 2008). The latter study, most relevant to data presented here, used Eukarya-specific PCR primers (Diez et al, 2001) to amplify 18S rRNA genes and analyze them through denaturing gradient gel electrophoresis profiling and sequence analysis.…”
Section: Subsurface Ecosystem Resilience Jm Yagi Et Almentioning
confidence: 99%
“…In these environments, eukaryotes interact with other microbes to form complex communities that play primary roles in both ecosystem structure and function (Fleet, 1999(Fleet, , 2003Lopez-Garcia et al, 2007). The first cultureindependent analysis of the fungal community populating a mammalian intestine revealed an unprecedented diversity and abundance of fungal species in the murine GI tract (Scupham et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Micro-eukaryotic species are ubiquitous components of various natural ecosystems, including hydrothermal environments (Gadanho et al, 2003;Lopez-Garcia et al, 2007), soil (van Elsas et al, 2000;Moon-van der Staay et al, 2006), the rumen (Ranilla et al, 2007) and food and beverage communities (Romano et al, 2003;Fleet, 2007;Quiros et al, 2008). In these environments, eukaryotes interact with other microbes to form complex communities that play primary roles in both ecosystem structure and function (Fleet, 1999(Fleet, , 2003Lopez-Garcia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%